Changes in organic C stability within soil aggregates under different fertilization patterns in a greenhouse vegetable field - Hao-an LUAN; Shuo YUAN; Wei GAO; Ji-wei TANG; Ruo-nan LI; Huai-zhi ZHANG; Shao-wen HUANG (Journal of Integrative Agriculture)
Knowledge of the stability of soil organic C (SOC) is vital for assessing SOC dynamics and cycling in agroecosystems. Studies have documented the regulatory effect of fertilization on SOC stability in bulk soils. However, how fertilization alters organic C stability at the aggregate scale in agroecosystems remains largely unclear. This study aimed to appraise the changes of organic C stability within soil aggregates after eight years of fertilization (chemical vs. organic fertilization) in a greenhouse vegetable field in Tianjin, China. Changes in the stability of organic C in soil aggregates were evaluated by four methods, i.e., the modified Walkley-Black method (chemical method), 13C NMR spectroscopy (spectroscopic method), extracellular enzyme assay (biological method), and thermogravimetric analysis (thermogravimetric method). The aggregates were isolated and separated by a wet-sieving method into four fractions: large macroaggregates (>2 mm), small macroaggregates (0.25–2 mm), microaggregates (0.053–0.25 mm), and silt/clay fractions (<0.053 mm). The results showed that organic amendments increased the organic C content and reduced the chemical, spectroscopic, thermogravimetric, and biological stability of organic C within soil aggregates relative to chemical fertilization alone. Within soil aggregates, the content of organic C was the highest in microaggregates and decreased in the order microaggregates>macroaggregates>silt/clay fractions. Meanwhile, organic C spectroscopic, thermogravimetric, and biological stability were the highest in silt/clay fractions, followed by macroaggregates and microaggregates. Moreover, the modified Walkley-Black method was not suitable for interpreting organic C stability at the aggregate scale due to the weak correlation between organic C chemical properties and other stability characteristics within the soil aggregates. These findings provide scientific insights at the aggregate scale into the changes of organic C properties under fertilization in greenhouse vegetable fields in China.